2019
DOI: 10.5398/tasj.2019.42.3.215
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Performance of Female Kacang Goats Supplemented by Mineral Under a Tethering Feeding System

Abstract: Inadequate feed intake and nutrient supply are associated with the suboptimal reproductive performance of Kacang goats reared using a traditional tethering system in the Pariaman region of Indonesia. The objectives of this study were to (i) identify reproductive problems in tethered female Kacang goats, (ii) assess crude nutrient and mineral composition of feed consumed by tethered goats, and (iii) evaluate the beneficial effects of mineral supplementation on reproductive performance of tethered female Kacang … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 17 publications
2
12
0
1
Order By: Relevance
“…These results indicate that providing LED light during incubation can improve hatch chick performance. This result is in accordance with that observed by Khalil (2009), who revealed that chicks hatched under light regime incubation appeared to be more active when compared with those hatched under dark incubation. Huth and Archer (2015) indicated that providing LED light during incubation can improve chick quality.…”
Section: Discussionsupporting
confidence: 93%
“…These results indicate that providing LED light during incubation can improve hatch chick performance. This result is in accordance with that observed by Khalil (2009), who revealed that chicks hatched under light regime incubation appeared to be more active when compared with those hatched under dark incubation. Huth and Archer (2015) indicated that providing LED light during incubation can improve chick quality.…”
Section: Discussionsupporting
confidence: 93%
“…That was possible with a different blood sampling process, where sampling for progesterone testing had been done before artificial insemination. As research by Khalil et al (2019a), who took blood samples for progesterone testing at 16 weeks in female goats, had a linear increase in serum progesterone levels with the addition of mixed minerals in the feed. However, Khalil et al (2019b) also reported that mineral supplementation did not affect serum progesterone levels of female cattle taken at 14 weeks.…”
Section: Pregnancy Ratementioning
confidence: 99%
“…However, there is still an imbalance between the supply and demand of meat. Most cattle production comes from smallholder farms, in which reproductive cattle tend to lack minerals, resulting in the low reproductive performance of animals (Agus and Widi, 2018;Khalil et al, 2019a). Minerals, both macro and trace minerals, play an essential function in regulating the reproduction and production of animals.…”
Section: Introductionmentioning
confidence: 99%
“…Mineral dalam rumen berfungsi untuk aktivitas pembentukan sel, aktivitas selulolitik, sintesis protein mikroba, dan juga untuk pertumbuhan mikroba yang akan berpengaruh langsung pada produktivitas serta efektivitas penggunaan nutrien pada ternak ruminansia (Durand & Kawashima 1979, Kwak et al 2020. Suplementasi mineral dapat meningkatkan status nutrisi, kesehatan, maupun reproduksi pada kambing kacang yang dicirikan dengan meningkatnya nilai hematologi darah, profil mineral darah dan keberhasilan kebuntingan (Khalil et al 2019), peningkatan produksi progesteron dan peningkatan kekuatan tulang dan gigi pada ternak (Muhtarudin & Liman 2006). Namun, suplementasi mineral komersial pada umumnya dapat meningkatkan biaya produksi sehingga tidak ekonomis dan diperlukan sumber mineral alami dengan memanfaatkan hijauan leguminosa lokal yang tinggi mineral.…”
Section: Pendahuluanunclassified